The Correspondence of Arthur Schnitzler and Raoul Auernheimer with Raoul Auernheimer's Aphorisms - Daviau, Donald G.; Johns, Jorun B. (UNC Studies in the Germanic Languages and Literatures, 1972)
This correspondence is a firsthand record of a literary and personal friendship that spanned the years 1906 to 1931. It is significant for both its insights into the lives and works of these two important writers and for its information concerning the eventful time in which they lived. The previously unpublished aphorisms of Auernheimer serve as a means of introducing a writer who had long been unjustly neglected. The aphorisms demonstrate the similarities of the two men in their broad range of interests as well as in the depth and perceptiveness of their thought, and help to explain Schnitzler's high regard for his friend.